2022
DOI: 10.1002/tal.1941
|View full text |Cite
|
Sign up to set email alerts
|

Robust structural control of a real high‐rise tower equipped with a hybrid mass damper

Abstract: In this paper, the robust control of a real high-rise tower is studied, using a newly proposed, in the structural control field, Robust Model Predictive Control scheme (RMPC). Two RMPC controllers were designed considering either displacement mitigation (RMPC 1 ) or power consumption efficiency (RMPC 2 ).The two controllers were compared to the benchmark, robustness-wise, H ∞ control scheme to demonstrate their relative performance. A number of stiffness and damping uncertainty scenarios were designed based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 87 publications
0
6
0
Order By: Relevance
“…To illustrate the efficiency of vibration control devices deployed in high-rise buildings, a review of various results obtained and presented in the literature is resumed in the two following tables [ 211 , 212 , 213 , 214 , 215 , 216 , 217 , 218 , 219 , 220 ]. Table 1 presents the results obtained when submitting high-rise benchmark buildings to earthquake excitation while equipping them with different control devices (best performances), and Table 2 shows the results of the same high-rise buildings submitted to wind excitations.…”
Section: Illustration Of Literature Resultsmentioning
confidence: 99%
“…To illustrate the efficiency of vibration control devices deployed in high-rise buildings, a review of various results obtained and presented in the literature is resumed in the two following tables [ 211 , 212 , 213 , 214 , 215 , 216 , 217 , 218 , 219 , 220 ]. Table 1 presents the results obtained when submitting high-rise benchmark buildings to earthquake excitation while equipping them with different control devices (best performances), and Table 2 shows the results of the same high-rise buildings submitted to wind excitations.…”
Section: Illustration Of Literature Resultsmentioning
confidence: 99%
“…It was found that the hybrid control method was efficient on limiting the peak acceleration of the long-span footbridge (case-study) within the serviceability limit to avoid human discomfort. Koutsoloukas et al (2022a) investigated the performance of an ATMD for the vibration control of a real high-rise tower. For the control law of the system, the authors derived a robust model predictive control (RMPC) algorithm.…”
Section: Active/hybrid Controlmentioning
confidence: 99%
“…The performance of the system was investigated during the Super Typhoon Hato and it was proven efficient for the vibration mitigation of the tower. Koutsoloukas et al (2022b) investigated the performance of the reinforcement learning deep deterministic policy gradient (DDPG) algorithm for the vibration dissipation of a real high-rise tower using an ATMD. The performance of the DDPG was compared to a PTMD and to a LQR.…”
Section: Active/hybrid Controlmentioning
confidence: 99%
“…To improve the seismic protection effect of a passive TMD, an active TMD with an actuator and direct power input to the primary structure is developed 28 . Though it has a better control effect, an active TMD will cost lots of power assumption and has a stability problem 29,30 . Compared to the active TMD, a semiactive TMD (STMD) with variable parameters needs less power assumption and has the advantage of inherent stability 31 .…”
Section: Introductionmentioning
confidence: 99%
“…28 Though it has a better control effect, an active TMD will cost lots of power assumption and has a stability problem. 29,30 Compared to the active TMD, a semiactive TMD (STMD) with variable parameters needs less power assumption and has the advantage of inherent stability. 31 Susheelkumar et al 32 proposed an adaptive TMD based on the fuzzy sliding mode.…”
Section: Introductionmentioning
confidence: 99%